2017
DOI: 10.1038/srep40969
|View full text |Cite
|
Sign up to set email alerts
|

The role of configurational disorder on plastic and dynamic deformation in Cu64Zr36 metallic glasses: A molecular dynamics analysis

Abstract: The varying degrees of configurational disorder in metallic glasses are investigated quantitatively by molecular dynamics studies. A parameter, the quasi-nearest atom, is used to characterize the configurational disorder in metallic glasses. Our observations suggest configurational disorder play a role in structural heterogeneity, plasticity and dynamic relaxations in metallic glasses. The broad configurational disorder regions distribution is the indicator of abundant potential deformation units and relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…The results are in good agreement with the characteristic time of the aged sample, as shown in Fig.3 (a). Therefore, the number of QNAs (N Q ), connected to the defects of clusters, reflects the correlation between local structure and dynamic heterogeneity [37]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results are in good agreement with the characteristic time of the aged sample, as shown in Fig.3 (a). Therefore, the number of QNAs (N Q ), connected to the defects of clusters, reflects the correlation between local structure and dynamic heterogeneity [37]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic heterogeneity such as β-relaxation process is also affected by nano-scale heterogeneity throughout the matrix 33 . The structural relaxation of these amorphous materials depends on the interconnected icosahedra cluster formation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed in both experimental and theoretical investigations that tension and compression modes possess different yield behaviors [5][6][7]. Although studying the plasticity in tension or compression is still a long-standing issue, it has been suggested that the yield difference could be related to the difference in plasticity between tension and compression [8,9]. Therefore, it is necessary to the mechanisms of deformation-in the yield stage, in particular-for both tension and compression modes.…”
Section: Introductionmentioning
confidence: 99%
“…To research the microscopic deformation mechanism of MGs, various specific structural concepts have been proposed, including shear transformation zones (STZs), flow units, free volumes (FVs), and flexible volumes [10][11][12][13][14]. It is known that, beginning with the yield stage, STZs begin to form shear bands, which contribute significantly to the plasticity in MGs [9,15]. STZs are the fundamental units of plasticity in amorphous metals, and are small clusters of randomly close-packed atoms that spontaneously and cooperatively reorganize under the action of an applied shear stress.…”
Section: Introductionmentioning
confidence: 99%